Determination of Critical MicelleDetermination of Critical Micelle Concentration (CMC) of Sodium Stearate and FESEM Study - Yadav, Brahamdeo; Bhattarai, Ajaya; Yadav, Chandradip Kumar (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
Correction: On 22 November 2024, the title of the article was changed and two authors were added. Surfactant is an organic compound with polar and nonpolar parts. The conductivity of sodium stearate surfactant in double distilled water has been studied by conductometric method at three temperatures (298.15, 308.15, and 318.15) K. The conductivity of the surfactant increases with an increase in temperature and concentration of solution. The critical micelle concentration (CMC) of sodium stearate determined at temperature 298.15 K is 0.00095 M using the easy plot software. FESEM image shows the morphological structure of the sodium stearate surfactant.